The Bill of Rights - Quiri, Patricia Ryon (New York Children's Press, 1998)
Chronicles how the Bill of Rights came to be, as well as the freedoms it guarantees, details each of the amendments, and demonstrates how some have affected contemporary life in the United States
American Corner
Includes bibliographical references (p. 44) and index
11
Keywords: United States -- Juvenile literature; Civil rights -- United States -- Juvenile literature; Civil rights; Constitutional amendments -- United States